2006
DOI: 10.1614/ws-05-067r.1
|View full text |Cite
|
Sign up to set email alerts
|

Integrating measurements of seed availability and removal to estimate weed seed losses due to predation

Abstract: To better understand seed predation and enhance weed seed losses in arable fields, we developed a conceptual model that integrates seed dispersal, seed burial, and seed demand, the three processes that determine the dynamics of summer annual weed seeds on the soil surface in late summer and autumn. Published and unpublished experimental data were used to parameterize a simulation model for a number of crop–weed combinations. Sensitivity analyses of models for giant foxtail in corn and soybean indicated that fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 30 publications
2
62
0
Order By: Relevance
“…More research is needed to clarify mechanisms that may lead to enhanced seed decay in organic systems. Surface weed seed removal by insect and small mammal predators from the soil surface is thought to substantially reduce weed seed banks, but predation rates can vary with tillage systems [77]. For example, Menalled et al [78] observed that activity density of granivorous carabids and removal of fall panicum (Panicum dichotomiflorum Michx.)…”
Section: Organic Zero Tillage Effects On Weedsmentioning
confidence: 99%
“…More research is needed to clarify mechanisms that may lead to enhanced seed decay in organic systems. Surface weed seed removal by insect and small mammal predators from the soil surface is thought to substantially reduce weed seed banks, but predation rates can vary with tillage systems [77]. For example, Menalled et al [78] observed that activity density of granivorous carabids and removal of fall panicum (Panicum dichotomiflorum Michx.)…”
Section: Organic Zero Tillage Effects On Weedsmentioning
confidence: 99%
“…The consumption of fruits by birds may not necessarily result in successful dispersal (MandonDalger et al 2004;Westerman et al 2006;Combs et al 2011). This is because some frugivorous birds are seed predators (Jordano 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Past research has, nonetheless, shown that the relative abundance and impact of seed predator guilds vary among habitats (Hulme 1998;Menalled et al 2000), and they can be affected by the type of crop management used (Carmona and Landis 1999;Gallandt et al 2005). Point estimates of seed predation do not accurately estimate the cumulative numbers of weed seed removed by predators because seed predation is affected by several temporally variable factors not easily assessed, including seed demand by predators, microsite predator density, the timing of seed dispersal, and seed residence time on the soil surface (Westerman et al 2006).…”
mentioning
confidence: 99%